A study on factor affecting the diagnosis of ischemic heart disease using logistic regression model / Nur Atikah Annual ... [et al.] - Annual, Nur Atikah; Abdullah, Norhedayu; Tuan Ab Aziz, Tuan Arisha Amani; Jamidin, Jaida Najihah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Ischemic heart disease (IHD) known as coronary heart disease is the most common form of heart disease. IHD occurs when the major blood vessels supplying the coronary arteries with blood, oxygen and nutrients to the heart become narrow by plaque. In addition, plaque forming by cholesterol also reduces the blood flow to the heart. Initially, a reduced blood flow may not cause any symptoms of IHD. However, as the plaque continues to build up in coronary arteries it may develop signs and symptoms of IHD such as feeling extremely fatigue, shortness of breath, chest pain and pressure, swelling in leg and feet, and difficulty sleeping. In addition, from 56.9 million deaths worldwide in 2016, more than half (54%) were due to the top 10 causes including IHD. IHD and stroke are the world's biggest killers, accounting for a combined 15.2 million deaths in 2016. These diseases have remained the leading causes of death globally in the last 15 years.